Transmission of methicillin-resistant Staphylococcus aureus in long-term care facilities and their related healthcare networks. Issue 1 (December 2016) - Harrison, Ewan; Ludden, Catherine; Brodrick, Hayley; Blane, Beth; Brennan, Gráinne; Morris, Dearbháile; Coll, Francesc; Reuter, Sandra; Brown, Nicholas; Holmes, Mark; O'Connell, Brian; Parkhill, Julian; et al.
Abstract Background Long-term care facilities (LTCF) are potential reservoirs for methicillin-resistantStaphylococcus aureus (MRSA), control of which may reduce MRSA transmission and infection elsewhere in the healthcare system. Whole-genome sequencing (WGS) has been used successfully to understand MRSA epidemiology and transmission in hospitals and has the potential to identify transmission between these and LTCF. Methods Two prospective observational studies of MRSA carriage were conducted in LTCF in England and Ireland. MRSA isolates were whole-genome sequenced and analyzed using established methods. Genomic data were available for MRSA isolated in the local healthcare systems (isolates submitted by hospitals and general practitioners). Results We sequenced a total of 181 MRSA isolates from the two study sites. The majority of MRSA were multilocus sequence type (ST)22. WGS identified one likely transmission event between residents in the English LTCF and three putative transmission events in the Irish LTCF. WGS also identified closely related isolates present in colonized Irish residents and their immediate environment. Based on phylogenetic reconstruction, closely related MRSA clades were identified between the LTCF and their healthcare referral network, together with putative MRSA acquisition by LTCF residents during hospital admission. Conclusions These data confirm that MRSA is transmitted between residents of LTCF and is both acquired and transmitted to others in referral hospitals and beyond. Our data present compelling evidence for the importance of environmental contamination in MRSA transmission, reinforcing the importance of environmental cleaning. The use of WGS in this study highlights the need to consider infection control in hospitals and community healthcare facilities as a continuum.